Inhibition of p38 MAPK during ischemia, but not reperfusion, effectively attenuates fatal arrhythmia in ischemia/reperfusion heart - Surinkaew S. (2014)
ABSTRACT:: The mitogen-activated protein kinases (MAPKs) play an important role in ischemia/reperfusion (I/R) injury. Previous evidence suggests that p38 MAPK inhibition before ischemia is cardioprotective. However, whether p38 MAPK inhibition during ischemia or reperfusion provides cardioprotection is not well known. We tested the hypothesis that p38 MAPK inhibition at different times during I/R protects the heart from arrhythmias, reduces the infarct size, and attenuates ventricular dysfunction. Adult Wistar rats were subject to a 30-minute left anterior descending coronary artery occlusion, followed by a 120-minute reperfusion. A p38 MAPK inhibitor, SB203580, was given intravenously before left anterior descending coronary artery occlusion, during ischemia, or at the onset of reperfusion. The results showed that SB203580 given either before or during ischemia, but not at the onset of reperfusion, decreased the ventricular tachycardia/ventricular fibrillation (VT/VF) incidence and heat shock protein 27 phosphorylation, and increased connexin 43 phosphorylation. The infarct size and cytochrome c level was decreased in all SB203580-treated rats, without the alteration of the total Bax/Bcl-2 expression. The ventricular function was improved only in SB203580-pretreated rats. These findings suggest that timing of p38 MAPK inhibition with respect to onset of ischemia is an important determinant of therapeutic efficacy. Copyright © 2013 by Lippincott Williams & Wilkins.